PENGARUH IMPLEMENTASI MODEL PBL (PROBLEM BASED LEARNING) TERINTEGRASI PEMBELAJARAN BERDIFERENSIASI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS KELAS V SD NEGERI 47/IV KOTA JAMBI - Tri Utami Widayati; Destrinelli; Muhammad Sofwan (Jurnal Penelitian Pendidikan IPA, 2025)
Based on the results of the pre-study, it is known that students' critical thinking skills are still not optimal. This is caused by the learning approach that has not been able to encourage the development of creativity and high-level thinking skills. To overcome this problem, the Problem Based Learning (PBL) approach combined with differentiated learning is offered as an innovative strategy to improve students' critical thinking skills. This study uses a quantitative approach with an experimental method. The design applied is Pre-Experimental with the form of One-Group Pretest-Posttest. The subjects of the study were fifth grade students of Elementary School 47/IV Jambi City. The critical thinking ability measurement instrument has been validated through expert judgment and limited trials. The indicators measured include the ability to identify problems, analyze arguments, evaluate information, draw logical conclusions, and make rational decisions. The results of the study showed a significant increase in critical thinking skills after the implementation of learning. The average pretest score of 53.23 increased to 75.32 in the posttest, which shows that the approach applied has a positive influence on the development of students' critical thinking skills. The integration of PBL with differentiated learning is not only able to encourage the improvement of critical thinking skills, but also provides space for individual learning needs, as well as increasing students' active involvement in the learning process. Theoretically, this study strengthens the relevance of constructivism theory in elementary education. Practically, the results of this study provide alternative effective and adaptive learning strategies for teachers in developing critical thinking skills in heterogeneous classes.